2010
DOI: 10.1002/eji.200940260
|View full text |Cite
|
Sign up to set email alerts
|

c‐Rel is crucial for the induction of Foxp3+ regulatory CD4+ T cells but not TH17 cells

Abstract: The NF-jB/Rel family member c-Rel was described to be required for the development of T H 1 responses. However, the role of c-Rel in the differentiation of T H 17 and regulatory CD41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
74
1
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 34 publications
6
74
1
1
Order By: Relevance
“…Isomura et al [19] found that c-Rel-deficient naïve CD4 1 T cells normally upregulated Foxp3 when stimulated in the presence of TGF-b. Although Visekruna et al [18] found that TGF-b-mediated Foxp3 induction in c-Rel-deficient peripheral CD4 1 T cells is severely hampered, this defect was not cell autonomous but rather due to their defective IL-2 production, because addition of exogenous IL-2 did rescue the impaired Foxp3 induction. In contrast, Ruan et al [21] show that iTreg differentiation from c-Reldeficient CD4 1 CD25 À T cells was impaired to some degree even in the presence of exogenous IL-2.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…Isomura et al [19] found that c-Rel-deficient naïve CD4 1 T cells normally upregulated Foxp3 when stimulated in the presence of TGF-b. Although Visekruna et al [18] found that TGF-b-mediated Foxp3 induction in c-Rel-deficient peripheral CD4 1 T cells is severely hampered, this defect was not cell autonomous but rather due to their defective IL-2 production, because addition of exogenous IL-2 did rescue the impaired Foxp3 induction. In contrast, Ruan et al [21] show that iTreg differentiation from c-Reldeficient CD4 1 CD25 À T cells was impaired to some degree even in the presence of exogenous IL-2.…”
mentioning
confidence: 94%
“…It has remained unclear, however, which NF-kB family members are required, whether NF-kB proteins directly and/or indirectly regulate the Foxp3 gene, and how they do so. Two reports in this issue of the European Journal of Immunology by Deenick et al [17] and Visekruna et al [18], together with four recent reports published elsewhere [19][20][21][22], have now addressed these issues and suggest that it is c-Rel that pioneers Foxp3 induction and hence Treg differentiation in the thymus.…”
mentioning
confidence: 96%
See 3 more Smart Citations